Abrazando el ciclo entre texturas y colores (2023)
Abrazando el ciclo entre texturas y colores is a research-creation project that arises from a concern related to the pain caused by menstruation and the impact it generates on people's emotions and psychological states. The project addresses a series of questions that arise in plastic action and poetic writing where relevant reflections are channeled to give way to a personal catharsis.